The Reign of James VI and I: the Birth of Britain - Croft, Pauline (History compass, 2003)
This article considers recent work over the past twenty-five years on the reign of James VI and I. The author argues that the multiple monarchy created by James VI of Scotland's accession to the English throne in 1603 was one of the greatest formative moments in the history of the British Isles, creating a political unit that endured until 1922, with the emergence of the Irish Free State. However, the structural problems of that multiple monarchy were also the major underlying cause of the ‘British’ civil war - fought out in Scotland and Ireland as well as England - that broke out in 1642.